Transient Decrease of Circulating and Tissular Dendritic Cells in Patients With Mycobacterial Disease and With Partial Dominant IFNγR1 Deficiency - Dotta, Laura; Vairo, Donatella; Giacomelli, Mauro; Moratto, Daniele; Tamassia, Nicola; Vermi, William; Lonardi, Silvia; Casanova, Jean-Laurent; Bustamante, Jacinta; Giliani, Silvia; Badolato, Raffaele (Frontiers in Immunology, 2020)
Interferon-γ receptor 1 (IFNγR1) deficiency is one of the inborn errors of IFN-γ immunity underlying Mendelian Susceptibility to Mycobacterial Disease (MSMD). This molecular circuit plays a crucial role in regulating the interaction between dendritic cells (DCs) and T lymphocytes, thus affecting DCs activation, maturation and priming of T cells involved in the immune response against intracellular pathogens. We studied a girl who developed at the age of 2.5 years a Mycobacterium avium infection characterized by disseminated necrotizing granulomatous lymphadenitis, and we compared her findings with other patients with the same genetic condition. The patient carried a heterozygous 818del4 mutation in the IFNGR1 gene responsible of autosomal dominant (AD) partial IFNγR1 deficiency. During the acute infection blood cells immunophenotyping showed a marked reduction in DCs counts, including both myeloid (mDCs) and plasmacytoid (pDCs) subsets, that reversed after successful prolonged antimicrobial therapy. Histology of her abdomen lymph node revealed a profound depletion of tissue pDCs, as compared to other age-matched granulomatous lymphadenitis of mycobacterial origin. Circulating DCs depletion was also observed in another patient with partial dominant IFNγR1 deficiency during mycobacterial infection. To conclude, partial dominant IFNγR1 deficiency can be associated with a transient decrease in both circulating and tissular DCs during acute mycobacterial infection, suggesting that DCs counts monitoring might constitute a useful marker of treatment response.